Pengaruh Leverage Dan Kepemilikan Manajerial Terhadap Manajemen Laba Pada Perusahaan Manufaktur - Krisnawati Zendrato; Hermaya Ompusunggu (LPPM Universitas Putera Batam, 2023)
The purpose of this study is to ascertain how managerial ownership and leverage affect earnings management. In this study, the purposive sampling method was used for sampling. The perception variable received a t count value of in accordance with the findings of the hypothesis test 0.785 < t table 1.655, and Sig 0.437 > 0.05. The competency variable obtained a t count value of 2.173 > t table 1.655, and Sig 0.012 < 0.05, so it can be concluded that managerial ownership variables have a significant impact on earnings management. As a result, It can be said that the leverage variable has little to no effect on managing earnings. It is possible to conclude that managerial ownership and leverage both significantly affect earnings management because the calculated f value is 33.488 with a significance of 0.000, which means that the significant value is less than the probability value, which is 0.05 or 0.000 0.05